The Effects of Physical Activity and the Consequences of Physical Inactivity in Adult Patients with Congenital Heart Disease During the COVID-19 Pandemic - Elettra Pomiato; Rosalinda Palmieri; Mario Panebianco; Giulia Di Già; Marco Della Porta; Attilio Turchetta; Massimiliano Raponi; Maria Giulia Gagliardi; Marco Alfonso Perrone (Journal of Functional Morphology and Kinesiology)
Background: The ongoing COVID-19 pandemic has infected more than 500 million people worldwide. Several measures have been taken to reduce the spread of the virus and the saturation of intensive care units: among them, a lockdown (LD) was declared in Italy on 9 March 2020. As a result, gyms, public parks, sports fields, outdoor play areas, schools, and multiple commercial activities have been closed. The consequences of physical inactivity can be dramatic in adult patients with congenital heart disease (ACHD), in which the benefit of regular exercise is well known. In this study, we investigated the effects of reduced physical activity during the COVID-19 pandemic on ACHD’s exercise capacity. Materials and Methods: Patients who performed exercise or cardiopulmonary exercise tests from October 2019 to February 2020 and one year after lockdown with the same protocol were retrospectively enrolled in our database. Inclusion criteria: ACHD patients aged ≥ 18 years old under regular follow-up. Exclusion criteria: significant clinical and/or therapeutic changes between the two tests; significant illness occurred between the two tests, including COVID-19 infection; interruption of one of the tests for reasons other than muscle exhaustion. Results: Thirty-eight patients (55.6% males) met the inclusion criteria. Before the lockdown, 17 patients (group A) were engaged in regular physical activity (RPA), and 20 patients (group B) had a sedentary lifestyle. After LD, in group A, (a) the weekly amount of physical activity reduced with statistical significance from 115 ± 46 min/week to 91 ± 64 min/week (−21%, p = 0.03); (b) the BMI did not change; (c) the duration of exercise test and VO2 max at cardiopulmonary exercise test showed a significant reduction after the LD. In group B, BMI and exercise parameters did not show any difference. Conclusions: The COVID-19 pandemic dramatically changed the habits of ACHD patients, significantly reducing their possibility to exercise. Our data analyzed in this extraordinary situation again demonstrated that physical inactivity in ACHD worsens functional capacity, as highlighted by VO2 max. Regular exercise should be encouraged in ACHD patients to preserve functional capacity.